Polymeric Nanomicelles of Soluplus® as a Strategy for Enhancing the Solubility, Bioavailability and Efficacy of Poorly Soluble Active Compounds - Pignatello, Rosario; Corsaro, Roberta (Current Nanomedicine, 2019)
Soluplus® is a commercially available graft amphipathic copolymer consisting of polyvinyl caprolactam, polyvinyl acetate, and polyethyleneglycol (13% PEG 6000/57% vinyl caprolactam/30% vinyl acetate). Among the various applications of this solubilizer excipient, produced by BASF, such as the production of amorphous solid dispersions of insoluble drugs, Soluplus® has shown to be able to form nano-sized micelles in water or other aqueous solutions, characterized by a very small diameter and an exceptionally narrow size distribution. These formulations allow to improve the solubility and physical stability in aqueous media of poorly soluble drugs. This review summarizes the recent data from literature on the methods of production and characterization of drugloaded nanomicelles based on Soluplus®, highlighting the potential fields of therapeutic application.
Keywords: nanomedicines